Prognostic Significance of Growth Pattern in Predicting Outcome of Opisthorchis viverrini-Associated Distal Cholangiocarcinoma in Thailand - Kunprom, Waritta; Aphivatanasiri, Chaiwat; Sa-ngiamwibool, Prakasit; Sangkhamanon, Sakkarn; Intarawichian, Piyapharom; Bamrungkit, Walailak; Thanee, Malinee; Prajumwongs, Piya; Loilome, Watcharin; Khuntikeo, Narong; Titapun, Attapol; Jareanrat, Apiwat; et al. (Frontiers in Public Health, 2022)
Distal cholangiocarcinoma (dCCA) is a rare type of CCA in Asia, even in Opisthorchis viverrini-prevalent Northeastern Thailand. The clinical ambiguity and imprecision of diagnosis surrounding this malignancy result in high mortality due often to advanced/metastatic disease on presentation. We aim to identify a prognostic factor that can improve the performance stratification and influence the outcome of dCCA patients after curative resection. A total of 79 patients who underwent curative-intended surgery for dCCA was enrolled. Possible risk factors for survival were analyzed with log-rank test, and independent factors with Cox regression model. dCCA patients were staged and classified according to the 8th edition the American Joint Committee on Cancer (AJCC) Staging Manual. Results were then compared with the revised classification employing the prognostic factor identified from multivariate analysis. Multivariate analysis revealed that growth pattern (p < 0.01) and distant metastasis (p = 0.012) were independent factors. Growth patterns comprise intraductal (ID), periductal infiltrating (PI), mass-forming (MF), and mixed types. When dCCA patients were grouped into those having good and poor outcomes (with and without ID components, respectively). The survival outcomes significantly differed among patients with and without ID components, which was better than with the 8th AJCC staging system in our cohort. Furthermore, Chi-square test showed that patterns without ID components (PI, MF, PI+MF) correlated with lymph node and distant metastasis. Therefore, classification of dCCA patients after curative-intended surgical resection based on growth pattern provides additional beneficial information for the prediction of survival in dCCA patients.